ANALISIS DESKRIPTIF MEMBACA PERMULAAN PADA MURID KELAS 1 SDI AL AZHAR 25 SEMARANG SEMESTER I TAHUN AJARAN 2023/2024 - Anis Fidiyaningrum; Ida Dwijayanti; Sumarno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The ability to read is a basic skill that every lower school student must have. Through reading, students can learn to understand the material of various subjects. This study aims to determine how the description of beginning reading of grade 1 students of SDI Al Azhar 25 semester I of the 2023/2024 academic year, with a sample of class IA students. The research method used is descriptive qualitative. The data collection techniques used were tests, observation, and documentation. The research instruments used were observation sheets for beginning reading, and documentation. Based on the results of the study, students' ability to read vowels was 100%. Students' ability to read consonant letters is mostly capable, which is 97%. Students' ability to read syllables (consonant + vowel) is mostly capable, namely 97%. Students' ability to read syllables (consonant+vowel+consonant) is mostly in the able category, namely 94.81%. Students' fluency in reading words (mixed vowels and consonants) is mostly in the able category, namely 92.59%. There are still some students who are still at the level of reading syllables, and have difficulty reading combined vowels and consonants. Therefore, further research is still needed on efforts so that the ability to read beginning in grade 1 students can be completed at the end of semester I.